Student Satisfaction Optimization Will Be The Quality of Learning Through The Exploration of Initial Decision Students Choose Private University in Bima City - Kartin, Aprianti; Amirulmukminin, Amirulmukminin (Journal of Education Research and Evaluation, 2019)
This study aims to reveal the role of the initial decision of students choosing tertiary institutions through physical evidence, reference groups and self-motivation and their impact on student satisfaction with the quality of learning. Research methods conducted using the survey method. The sample in this study were active students at private universities in the city of Bima as many as 379 respondents using the Proportionate Stratified Random Sampling technique. Data analysis and hypothesis testing using regression analysis with the help of SPSS Version 20 for windows. The results showed that aspects of physical evidence, reference groups and self-motivation had a positive and significant role in the decision of students in choosing tertiary institutions. The impact of these student decisions also has a positive and significant effect on student satisfaction with the quality of learning of selected tertiary institutions. The implications of this study are directed to be able to maximize the dimensions that influence students' initial decisions in choosing tertiary institutions so as to optimize student satisfaction on the quality of learning starting from the input, process and output of learning-oriented to the aspects of services that are directly felt by students as recipients of educational services. Keywords: Quality of Learning, Student Satisfaction,  Decisions to Choose a College